It's not healthy if they don't eat it: school lunch plate waste and strategies to increase vegetable consumption - Smith, Stephanie Laine, author; Cunningham-Sabo, Leslie, advisor; Auld, Garry, committee member; Harris, Mary, committee member; Kelly, Kathleen, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.